Impact of Leisure Reading on the Stress Levels in Medical Students Nihan Farooq - Sana Viqar, Maham Bakhtyar, Nihan Farooq, Sana Viqar, Maham Bakhtyar, Nihan Farooq (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Medical students experience a considerable level of stress throughout the course of their academic studies. It is imperative for students to adopt strategies to deal with various stressors. The objective of this study is to find out the impact of leisure reading on the stress levels in medical students. Methods: A cross sectional study was conducted in Rawalpindi Medical University from December 2016 to March 2017 which comprised of 405 students enrolled in the first three academic years. The questionnaire used in the study included 10-item Perceived Stress Score Test in addition to questions related to leisure reading, its types and frequency. Data was entered and analyzed on Statistical Package for Social Sciences (SPSS) version 22. Chi square test and Independent Samples t test were applied to compare stress scores with leisure reading at 5% level of significance. Results: The mean perceived stress score in medical students was found to be 20.05 ± 6.751. Out of 405 students, 233 (57.5%) students read books in their leisure time, whereas 172 (42.5%) students did not read (p=0.01). Proportion of students with low and moderate perceived stress was similar in both reader and non-reader category. However, it was revealed that readers with high perceived stress scores were (14.2%) and non-readers with high perceived stress scores were 41 (23.8%), this difference being statistically significant (p=0.03). There was no statistical association between leisure reading, as well as stress scores with factors like boarding status, gender, year of MBBS or financial and personal issues (p>0.05). Conclusion: Leisure reading has an impact on the stress levels in medical students. High perceived stress was shown by fewer students among the readers and more among the non-readers. This study suggests that leisure reading can be adopted by students as a healthy activity to cope with stress. The benefit of reading in reducing stress in medical students should be further studied.